Analisis Kinerja Keuangan Perusahaan Ditinjau dari Rentabilitas, Likuiditas dan Solvabilitas - Mu'arifin, Hidayatul; Irawan, Peri (Ridwan Institute, 2021)
The purpose of this study is to analyze the financial performance of PT Sentul City Tbk and its Subsidiaries in 2018-2019 in terms of profitability, liquidity and solvency and to determine the effect of profitability, liquidity and solvency on Company Value both simultaneously and partially. The research object was carried out on the official website of PT Sentul City and at LQ45. The type of data used is secondary data. Methods of data collection using quantitative methods and descriptive methods, namely data in the form of exact numbers and analyze data from the company's financial statements. And it can be concluded that the level of analysis of profitability, liquidity and solvency is very influential on Firm Value and from the analysis the company can be categorized in a multi-state condition or not.